Multiple extracellular activities in Drosophila egg perivitelline fluid are required for establishment of embryonic dorsal-ventral polarity. - Stein, D.; Nusslein-Volhard, C. (Cell, 1992)
Twelve maternal effect genes (the dorsal group and cactus) are required for the establishment of the embryonic dorsal-ventral axis in the Drosophila embryo. Embryonic dorsal-ventral polarity is defined within the perivitelline compartment surrounding the embryo by the ventral formation of a ligand for the Toll receptor. Here, by transplantation of perivitelline fluid we demonstrate the presence of three separate activities present in the perivitelline fluid that can restore dorsal-ventral polarity to mutant easter, snake, and spätzle embryos, respectively. These activities are not capable of defining the polarity of the dorsal-ventral axis; instead they restore structures according to the intrinsic dorsal-ventral polarity of the mutant embryos. They appear to be involved in the ventral formation of a ligand for the Toll protein. This process requires serine proteolytic activity; the injection of serine protease inhibitors into the perivitelline space of wild-type embryos results in the formation of dorsalized embryos.